KARAKTERISTIK EKOSISTEM RUMEN SAPI YANG DIBERI SILASE BERBASIS JERAMI JAGUNG - Agus Suprayogi; Muhammad Mukhtar (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2020)
The purpose of this study was to determine the characteristics of the rumen ecosystem of Bali cattle which were given Complete Silage Feed with the main ingredient being corn straw. This study was used twelve Balinese cattle which are grouped based on body weight. Bali cattle body weight groups are K1: 160 Kg - 170 Kg; K2: 171 Kg - 187 Kg; and K3: 204 Kg - 220 Kg. This study used a randomized block design (RBD) with four treatments and three heavy groups. Feed care: R0 (85% Straw corn + 15% concentrate as a control); R1 (70% Corn straw + 5% Gamal leaves + 25% concentrate); R2 (65% Corn straw + 10% Gamal leaves + 25% concentrate); and R3 (60% corn straw + 15% Gamal leaves + 25% concentrate). Data were analyzed using analysis of variance, through the Exel Program. significant test using LSD. The parameters observed were pH, NH3 (ammonia), and VFA (fatty acids). Based on the results of the study showed the pH value of the rumen fluid was normal (6.80-6.90), the concentration of Ammonia produced: 13.67-31.64. Total VFA production is 70-90 mM, this VFA increases in line with an increase in Gamal leaves by 15%. Feeding Complete Silage from corn straw to Bali cattle does not affect the pH, NH3, and VFA values in the rumen.